Impact of the removal of patient co-payments for antiretroviral therapy (ART) on out-of-pocket expenditure, adherence and virological failure among Australian adults living with HIV. Issue 9 (September 2021) - Lee, Evelyn; Mao, Limin; de Wit, John; Rule, John; Carr, Andrew; Siefried, Krista J; ,
Highlights: Removal of patient co-payments for ART did not reduce total out-of-pocket healthcare expenditure Co-payment removal did not improve ART adherence or reduce HIV virological failure Participants receiving concessional government benefits experienced an increase in HIV related expenditures Participants with the lowest income remain vulnerable to the relative high-cost burden of HIV care Further, larger studies are warranted Abstract: Background: : In 2015, New South Wales (Australia) removed patient co-payments for ART of HIV. We hypothesized the policy change would reduce overall out-of-pocket (OOP) healthcare expenditure, improve ART adherence, and better maintain HIV suppression. Methods: Using data from a national, 2-year prospective study of adults with HIV on ART (n=364) (2013-2017), we compared OOP healthcare expenditure, ART adherence, and virological failure (VF) in participants subject to the co-payment policy change with participants from other jurisdictions who never paid, and who always paid, co-payments. We used fixed effects regression models to compare outcomes, and incidence rates for VF. Results: : Although ART co-payments declined, there was no significant change in total OOP healthcare expenditure in participants ceasing co-payments compared to those who continued (adjusted coefficient 0.09, 95% CI -0.31 to 0.48). Co-payment removal did not significantly reduce suboptimal ART adherence (from 17.5% to 16.3%) or VF (from 5.0 to 3.7 episodes per-100-person-years). Participants in the lowest income group but not receiving concessional government benefits incurred a non-significant increase in total OOP healthcare expenses; while concessional participants experienced a significant increase in non-ART HIV healthcare costs after the policy changed. Conclusion: : In this population, ART co-payments represented a small proportion of OOP healthcare expenditure. Its removal did not materially impact ART adherence or VF, although the study was not powered to detect these.